Keterampilan Menyimak Naskah Drama dengan Menggunakan Media Film 17 Selamanya pada Siswa Kelas VIII SMPN 1 Banggai Utara - Haryadi Haryadi; Zuhra Sl. Datu; Agus Nuryatin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Students' listening skill activities are expected to be able to interpret the speech that lies in the drama script using film 17 forever and students must pay attention to three stages in listening to drama scripts using film 17 forever, namely, (1) explaining student activities in listening to drama using the use of film. film media 17 forever, (2) Expressing students' ability to listen to drama scripts using 17 forever film media, (3) saying students' responses to using 17 forever film media in listening to drama scripts. Teachers and students of class VIII B totaling 25 people were the subjects in this study. The results of the research on discovery 1 in the first cycle, the score given by the two observers after being accumulated is the average score of students are 68 (active). In cycle II, there was an increase in the score given by the observer and the average score for student activities. The total score is given by the two observers, as well as the average score for student learning activities, is 70. In discovery 2 there is a cycle I average value of student learning outcomes listening to drama scripts, which is 80.0, whereas in cycle II there is an increase to 85.0. The increase occurred from cycle I to cycle II of 4.80, not only that, the number of students who completed exploring education from cycle I to cycle II faced significant changes. In cycle I, from the total number of villages, only 20 people (80.0%) got a complete score. On the other hand, in cycle II, the totality of students found (100%) complete education by listening to drama scripts on film media 17 forever. (In discovery 3) the first cycle of students shared a positive response (responsive) to the education of listening to drama scripts using film 17 forever with an average value of 79.02 In the second cycle, the average value given by students to this education increased to 80.10 (responsive). So that it can be concluded from the initial, second, and third findings, and the explanation above, it can be concluded that research on the use of film 17 forever in education by listening to drama scripts can increase the learning outcomes of class VIII B students of SMPN 1 Banggai Utara.